2020
DOI: 10.1080/09540121.2020.1837722
|View full text |Cite
|
Sign up to set email alerts
|

Unintended uses, meanings, and consequences: HIV self-testing among female sex workers in urban Uganda

Abstract: Female sex workers (FSWs) are at increased risk of HIV and face significant barriers to clinic-based HIV testing, including provider stigma and privacy constraints. HIV self-testing (HIVST) has been proven to significantly increase HIV testing among FSWs. Less is known, however, about how FSWs make meaning of oral-fluid HIV self-tests, and the unintended ways they use and understand this novel technology. From October 2016 to March 2017, we conducted 61 indepth interviews with FSWs (n = 31) in Kampala, Uganda.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…These findings highlight the complexity of utilizing word-of-mouth peer systems to disseminate intervention information, thereby emphasizing the need for intervention evaluations. While peer instruction on HIVST use was intended by the intervention, direct peer assistance conducting HIVST (e.g., timing, and interpreting HIVST results) was not intended and may pose risk of testing coercion or involuntary HIV status disclosure [ 15 ]. Furthermore, word-of-mouth peer networks were also prone to the quick spread of misinformation surrounding HIV risk and HIVST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings highlight the complexity of utilizing word-of-mouth peer systems to disseminate intervention information, thereby emphasizing the need for intervention evaluations. While peer instruction on HIVST use was intended by the intervention, direct peer assistance conducting HIVST (e.g., timing, and interpreting HIVST results) was not intended and may pose risk of testing coercion or involuntary HIV status disclosure [ 15 ]. Furthermore, word-of-mouth peer networks were also prone to the quick spread of misinformation surrounding HIV risk and HIVST.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized implementation trial in this setting found that peer-delivered oral-fluid HIV self-testing (HIVST) significantly increased recent and repeat HIV testing among FSWs compared to standard facility-based testing [ 4 ]. Additionally, FSWs in this trial described peer-delivered HIVST as desirable because it increased privacy, convenience (including time and cost), sense of control, and confidentiality [ 15 , 16 ]. Although this model of peer delivery has been found to be appropriate among FSWs in this setting, little is known about how FSW social support structures (e.g., informational, instrumental, and emotional support) influence the delivery and uptake of peer-delivered HIV prevention interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In one study on which the first author collaborated, data revealing unintended consequences emerged from the field during the data collection. Consequently, the research team was compelled to address the issue even though it was not in their initial objectives [65]. Researchers in this situation may have to re-analyze their data to meet this new objective, which ultimately may turn out to be more timeconsuming and costly.…”
Section: Validate the Classification Of Intended Versus Unintended Comentioning
confidence: 99%
“…The level of desirability can vary when the perceptions of decision-makers are compared with those of street-level workers, who have different goals and needs. Operationalizing these concepts imposes difficult choices on research teams, but examples of how to do it are available in the literature [48][49][50]65].…”
Section: Determine the Study's Perspectivementioning
confidence: 99%
“…HIV self-testing (HIVST), a process in which an individual performs an HIV rapid diagnostic test and interprets the result in private, is highly acceptable, convenient and discreet and may be empowering for SW not accessing traditional HIV testing services [7,8]. This emerging strategy has been shown to significantly increase recent and repeat HIV testing among SW [9,10], and is being scaled up for key populations in high HIV prevalence settings [11]. The WHO also recommends oral pre-exposure prophylaxis (PrEP) for HIV-negative persons at substantial and ongoing HIV risk [12].…”
Section: Introductionmentioning
confidence: 99%